Investigation on the Sodium and Potassium Tetrasalts of 1, 1, 2, 2‐Tetranitraminoethane. Issue 24 (10th November 2016) - Born, Maximilian; Härtel, Martin A. C.; Klapötke, Thomas M.; Mallmann, Mathias; Stierstorfer, Jörg
Abstract : With respect to high‐energy dense materials with high oxygen‐content, the tetrasodium salt of 1, 1, 2, 2‐tetranitraminoethane as monohydrate Na4 TNAE· H2 O (4 ) and the tetrapotassium salt as dihydrate K4 TNAE· 2H2 O (5 ) were synthesized and reported for the first time together with their crystal structures at 173 K. Whilst4 cannot be dehydrated the crystal water content of5 can be removed irreversibly at 160 °C to obtain K4 TNAE (6 ) as demonstrated by DTA and TGA measurements. K4 TNAE (6 ) was demonstrated using the small scale reactivity test to be a inferior explosive to RDX and CL‐20. However the anionic nitramine compound was measured to be less toxic against Vibrio fischeri than RDX (EC50 : 240 mg· L –1 ) with respect to its EC50 value above 15070 mg· L –1 . This demonstrates that the introduction of anionic nitramine moieties is a promising concept for the stabilization of energetic materials with lower toxicity. Abstract :